Immune nutrition and exercise: Narrative review and practical recommendations - Williams, N. C.; Killer, S. C.; Svendsen, I. S.; Jones, A. W. (European Journal of Sport Science, 2019)
Evidence suggests that periods of heavy intense training can result in impaired immune cell function, and whether this leaves elite athletes at greater risk of infections and upper respiratory symptoms (URS) is still debated. There is some evidence that episodes of URS do cluster around important periods of competition and intense periods of training. Since reducing URS, primarily from an infectious origin, may have implications for performance, a large amount of research has focused on nutritional strategies to improve immune function at rest and in response to exercise. Although there is some convincing evidence that meeting requirements of high intakes in carbohydrate and protein and avoiding deficiencies in nutrients such as vitamin D and antioxidants is integral for optimal immune health, well-powered randomised controlled trials reporting improvements in URS beyond such intakes are lacking. Consequently, there is a need to first understand whether the nutritional practices adopted by elite athletes increases their risk of URS. Second, promising evidence in support of efficacy and mechanisms of immune-enhancing nutritional supplements (probiotics, bovine colostrum) on URS needs to be followed up with more randomised controlled trials in elite athletes with sufficient participant numbers and rigorous procedures with clinically relevant outcome measures of immunity.